Production of xylitol by candida krusei using xylose from oil palm empty fruit bunch (opefb) as a substrate - Nur Putih Ikhram Ilani, Alias (2013)
The most important application of xylitol is its use as an alternative sweetener in foods for diabetic patients. Besides that, xylitol also important are as an anticariogenic agent in tooth paste formulations, as thin coatings on chewing vitamin tablets, in mouth washes, beverages and in bakery products (Rahman et al., 2006). There are few ways to gain this product. One of the ways is by using alkali extraction process. In this process, the main important reagent is Sodium Hydroxide (NaOH-5%) which will be used to gain the desire product (Sun et al., 1999). Besides that, the other method that can be used to get this product is by using acid hydrolysis and as this process is simpler, and this experiment will be done by using this acid hydrolysis method to obtain the product. By using acid hydrolysis process, the EFB will put in contact with the acid and as the reaction occur, xylose will be produced. The product obtained then will be filtrate to separate the solution with the insoluble EFB during the experiment (Rahman et al., 2006). In order to produce xylitol from xylose, fermentation process using suitable microorganism is required. Therefore, xylose will undergo fermentation process by using Candida krusei a type of yeast which can convert xylose to xylitol after certain period time with suitable culture media (Mohamad et al., 2009). There are three parameters that were used in this experiment which are the effect of time of hydrolysis, effect of pH and effect of amount of hydrolysate to the production of xylitol. From the result obtained it was found that the duration time for acid hydrolysis was found to be 150 minutes, the pH was 2 and the value of the hydrolysate was found to be 50 mL. All these parameter value lead to the high production of xylitol.